Special Event Impacts for Direct Stakeholders: Perspectives of Indonesia’s Independence Day Celebration - Tandaju, Teddy; Sumual, Loureine; Korompis, Merry (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
Indonesia’s Independence Day Celebration (IIDC) as one of great assets to attract better tourism development. The increase in the number of high visits is basically a potential that must continue to be developed.  The IIDC has its own uniqueness and distinctive aspects for tourists to experience or participate. IIDC is celebrated throughout Indonesia with various cultural activities according to each province’s local wisdoms. This event is a national joy and certainly reoccurs annually. This study aims to discuss the importance of holding an event as a tourist attraction together with its impacts on direct stakeholders and how the event or festival of IIDC commemoration can be a sustainably profitable tourist attraction for Indonesia. This study used descriptive method, and the data collected through literature review taken from various sources such as academic books, journals, newspaper articles, and publication in electronics media. The results found that IIDC would serve as a potential sustainable tourist attraction which will breed great economic output as well as building better community-based tourism activities since it is celebrated annually. IIDC is considered a very special event which has the potential of boosting tourism development in Indonesia.